Mechanism of Polychlorinated Dibenzo-p-dioxins Degradation by Ozone - Wen, Zhengcheng; Kang, Puzi; Cai, Benxiao; Wang, Zhihua; Xu, Jiangrong; Cen, Kefa (Asian Journal of Chemistry, 2015)
Despite of its fundamental importance, the reaction mechanism of polychlorinated dibenzo-p-dioxins destruction by using ozone still lacks detailed investigation. As a well-established method for investigating the chemical reactions, quantum chemical calculations were employed to investigate this reaction mechanism. Theoretical results showed that polychlorinated dibenzo-p-dioxins were gradually destructed by ozone via the cleavages of the C=C bonds and aromatic rings and the calculated activation energies were about 12 kcal/mol by the UB3LYP ++/6-311G(d,p)//UB3LYP/6-31G(d) method. In order to examine the rationality of the theoretical results, the experiment of the polychlorinated dibenzo-p-dioxins destruction by using ozone was also performed in this work. It was found that increase in the chlorite atoms on polychlorinated dibenzo-p-dioxins increased the theoretical activation energies. Whereas in the experimental results the removal efficiencies were found decreased. Obviously, the increasing of activation energies leads to the descending of removal efficiencies. It is suggested that the theoretical results were backed up quite well by the experimental results.